Ventilación mecánica en el síndrome de dificultad respiratoria en neonato pretérmino. - Moreira Daza, Stefanie Yulissa (2020)
The present clinical case is based in mechanical ventilation in a premature patient of 36 weeks of gestation diagnosed with a respiratory distress syndrome due to deficiency of pulmonary surfactant, which triggers a symptom picture where his respiratory muscles are affected, the patient is found unstable, presents dyspnea, hypercapnia, is tachypneic and tachycardia. For the diagnosis of this type of premature patient, different diagnostic methods were used, such as; chest radiography, arterial blood gas, blood count, in addition, using the APGAR and SILVERMAN-ANDERSON scale tests, which were effective and very helpful in obtaining a definitive diagnosis and thus using the correct treatment on time. The treatment used in this patient with respiratory distress syndrome due to pulmonary surfactant deficiency is invasive mechanical ventilation that exists to support breathing, which aims to improve oxygen saturation, correct hypercapnia and improve gas exchange in the alveoli. In this type of patient, the use of the synchronized intermittent mandatory ventilation (SIMV) mode is recommended. The clinical case has the general objective of establishing the benefit of mechanical ventilation and respiratory distress syndrome in preterm infants, in addition to being able to check the severity and determine the treatment of respiratory distress syndrome in this type of patient.